Pengaruh Firm Size, Dividen, dan Earnings Per Share (EPS), terhadap Return Saham pada Perusahaan yang Terdaftar Dalam Indeks Saham IDX Sharia Growth (IDXSHAGROW) Periode 2022-2024 - Istiqomah, Nurul; Dini Rahmayanti (Jurnal Bisnis Islam dan Kewirausahaan, 2026)
This study aims to examine the effect of Firm Size, Dividends, and Earnings Per Share (EPS) on stock returns in companies listed in the IDX Sharia Growth index (IDXSHAGROW) for the 2022-2024 period. The research population consisted of 30 companies, and through purposive sampling, a sample of 22 companies (66 observations) was obtained. The analysis method used is panel data regression with the best model being the Fixed Effect Model (FEM). The results show that simultaneously, Firm Size, Dividends, and EPS have a significant effect on stock returns. Partially, Firm Size and EPS have a positive and significant effect on stock returns. Conversely, Dividends have a negative and insignificant effect on stock returns. The Adjusted R-Square value of 0.396 indicates that the independent variables are able to explain the variation in stock returns by 39.6%, while the rest is explained by other factors outside the model. These findings indicate that investors in the IDXSHAGROW index consider company scale and profitability more than dividend distribution in making investment decisions.